When is the individually rational payoff in a repeated game equal to the minmax payoff? - Olivier Gossner; Johannes Hörner (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2006)
We study the relationship between a player's (stage game) minmax payoff and the individually rational payoff in repeated games with imperfect monitoring. We characterize the signal structures under which these two payoffs coincide for any payoff matrix. Under a full rank assumption, we further show that, if the monitoring structure of an infinitely repeated game 'nearly' satisfies this condition, then these two payoffs are approximately equal, independently of the discount factor. This provides conditions under which existing folk theorems exactly characterize the limiting payoff set.
Keywords: 330; Wiederholte Spiele; Signalling; Theorie